Perceptions of NIRSA Employees Relating to the Presence of Sexual Harassment and Related Offensive Behavior (Quid Pro Quo) within College Recreation Department Workplaces. Issue 1 (April 2013) - Stier, William F.; Schneider, Robert C.; Kampf, Stephen; Gaskins, Brady
This article summarizes the responses of NIRSA employees in terms of their perceptions of specific unwanted sexual harassment activities and behavior and the extent to which a quid pro quo (sex for favors) environment or situation exists within their respective work places. This is the second part of a four-part North American investigation of College Recreation Departments Workplaces on the subject of sexual harassment in the workplace. Examination and comparison of the data were made in terms of a) whether such behavior takes place, b) the types (examples) of sexual behaviors deemed to be part of quid pro quo expectations of sexual favors, as well as c) the frequencies of such behavior. Analysis of the data was based on the respondent's gender, gender of their supervisor, and marital status. The study revealed that sexual harassments conduct in terms of quid pro quo behavior was not thought to exist in any meaningful manner in the college recreational programs as perceived by those individuals employed (in a variety of positions and areas of responsibilities) within such departments.